Perspectives in allergen immunotherapy: 2017 and beyond - Pfaar, Oliver (Allergy, 2018)
The Future of the Allergists and Specific Immunotherapy (FASIT) workshop provides a regular platform for global experts from academia, allergy clinics, regulatory authorities and industry to review developments in the field of allergen immunotherapy (AIT). The most recent meeting, held in February 2017, had two main themes: advances in AIT and hot topics in AIT from the regulatory point of view. The first theme covered opportunities for personalized AIT, advances in adjuvants and delivery systems, and the development of new molecules and future vaccines for AIT. Key topics in the second part of the meeting were the effects of the enactment of European Directive 2001/83 on the availability of allergens for therapy and diagnosis across the EU, the challenges of conducting Phase 3 studies in the field, the future role of allergen exposure chambers in AIT studies and specific considerations in performing AIT studies in the paediatric population. Finally, the group highlighted the forthcoming EAACI guidelines and their particular importance for the standardization of practice in the treatment of allergies. This review presents a comprehensive insight into those panel discussions and highlights unmet needs and also possible solutions to them for the future.
Gesehen am 18.09.2019
First published: 24 November 2017